CPC-018 AnETh: An Original Tool For Assessing, Promoting and Improving Your Patient Education (PE) Programme. (12th March 2013) - Federspiel, F; Herbin, L; Alby, MN; Beauvais, C; Carrat, F; Debrix, I
Abstract : Background: In France, the annual self-assessment of PE programmes is recommended by the Regional Health Agencies. This analytical approach, necessarily time-consuming and structured, is a challenge for any team. However, it is a preliminary step in any process of qualitative and quantitative improvement. Purpose: First to provide a tool enabling teams to formalise and describe their work processes and to record work done and resources data in order to identify margins of progress leading to an improved action plan. Materials and Methods: A survey of quality criteria was conducted according to the recommendations available in France about PE programmes. The quantitative criteria were those requested by regional agencies. Several successive versions have been developed. Each was tested by a group of programme coordinators and updated as necessary. Results: The final tool is provided in the form of a user-friendly Excel document. The first input sheet is simply used to identify the programme. The following three input sheets are designed to record qualitative data (process), quantitative data (tasks accomplished), and the achievement of programme objectives (effectiveness). The output summary sheet shows graphical results and highlights the strengths and weaknesses of the programme, as well as quantitative changes from the previous year. The last sheet allows you to edit a report containing the main recorded items. Conclusions: AnETh appears to be easy to use and provides an original interface for identifying and evaluating PE activities in order to improve actions. It provides a simple method for meeting the requirements of self-assessment and certification and, in the current context of financial constraints, it may be used as a useful activity and resources report. Future versions may incorporate an interface with the usual recording software, in order to skip data collection. No conflict of interest.